2012
DOI: 10.3390/coatings2010008
|View full text |Cite
|
Sign up to set email alerts
|

Ion-Induced Surface Modification of Magnetically Operated Contacts

Abstract: Abstract:A study has been made of permalloy (iron-nickel) contacts of reed switches before and after ion-induced surface modification using atomic force and optical microscopy, Auger electron and X-ray photoelectron spectroscopy. It has been found that the formation of surface nitride layers enhances corrosion and erosion resistance of contacts. We proposed to produce such layers directly into sealed reed switches by means of pulsing glow-discharge nitrogen plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The duration of the single ion-plasma treatment was 30 s with 30 s pause between each single treatment, and the total number of such treatments was as high as 30. In that case, the reed switch is considered as a simple diode system, where blades act as electrodes (cathode and anode), and the glass bulb filled with nitrogen serves as a working chamber (for detail, see [6][7][8][9] and references cited therein).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The duration of the single ion-plasma treatment was 30 s with 30 s pause between each single treatment, and the total number of such treatments was as high as 30. In that case, the reed switch is considered as a simple diode system, where blades act as electrodes (cathode and anode), and the glass bulb filled with nitrogen serves as a working chamber (for detail, see [6][7][8][9] and references cited therein).…”
Section: Resultsmentioning
confidence: 99%
“…The main difference of the prototype against a standard device is the absence of the goldruthenium electrodeposited coatings on the contact surfaces. Instead of those, nitrogen-containing iron/nickel coatings were fabricated directly in reed switches using pulsed ion-plasma treatment [6][7][8][9]. The contacts (blades) were pressed with vacuum-melt permalloy (Ni 52 wt %, Fe 48 wt %) wires by Dilaton™, degreased, and annealed in hydrogen atmosphere.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous works [2][3][4], we showed that contamination and defects of the contacting surfaces of reed switches affected their conductivity and breakdown voltage. Reed switches belong to the class of electromechanical devices of millimeter dimension.…”
Section: Introductionmentioning
confidence: 89%